The multiple-race population of the United States: Issues and estimates - Goldstein, Joshua R. (The National Academy of Sciences, 2000)
This paper presents national estimates of the population likely to identify with more than one race in the 2000 census as a result of a new federal policy allowing multiple racial identification. A large number of race-based public policies—including affirmative action and the redistricting provisions of the Voting Rights Act—may be affected by the shift of some 8–18 million people out of traditional single-race statistical groups. The declines in single-race populations resulting from the new classification procedure are likely to be greater in magnitude than the net undercount in the U.S. census at the center of the controversy over using census sampling. Based on ancestry data in the 1990 census and experimental survey results from the 1995 Current Population Survey, we estimate that 3.1–6.6% of the U.S. population is likely to mark multiple races. Our results are substantially higher than those suggested by previous research and have implications for the coding, reporting, and use of multiple response racial data by government and researchers. The change in racial classification may pose new conundrums for the implementation of race-based public policies, which have faced increasing criticism in recent years.